The Simulacrum or the Treacherous Copy: A Reading of "Jidarriyah" by Mahmoud Darwish and "Nuqoush 'ala Jidarriyah Mahmoud Darwish" by Al-Mutawakil Taha - Quttous, Bassam (Dirasat: Human and Social Sciences, 2025)
Objectives: to combine critical grounding of Simulacrum, iconic copy, and application examined through two poetic models: Mahmoud Darwish in his collection "Jidarriyah," as the original copy; and the Palestinian poet Al-Mutawakil Taha’s "Nuqoush 'ala Jidarriyah Mahmoud Darwish," the second copy that he wrote as a simulation with "Jidarriyah,". Methods: The study adopts analytical criticism with a philosophical cognitive background as a methodology for examining the collections. Results: The study revealed that Darwish, original copy auther, was able to write himself sincerely, while second poet, Taha, wrote himself through the other. The second copy attempted to engage in dialogue with the first copy, but it failed to reach the essence of the iconic copy. It was closer to assimilation and was termed "simulacrum copy" because of internal strength contained in the first copy, derived from "power of self-explosion", not overshadowed by the trickery of the second text. Conclusions: The study focused on distinguishing between authentic identity of Darwish's creative work and ambiguous identity of Taha's collection. After studying two copies, it was confirmed that simulacrum copy did not rise to original copy. The study recommends investigating other poetic texts amenable to critical study.